Motor outcomes in young children pre‐and one‐year post‐liver transplant. (7th December 2021) - Patterson, Catherine; So, Stephanie; Rogers, Alaine; Ng, Vicky L.
Abstract: Background: Motor skill acquisition plays an important role in physical activity participation and overall social and physical health. Limited studies have examined motor development in children pre‐and post‐liver transplant (LT). Methods: Retrospective review of motor outcomes in children <6 years old with cholestatic liver disease assessed pre‐and 1‐year post‐isolated LT. Measures include Alberta Infant Motor Scale and Peabody Developmental Motor Scales (gross motor quotient (GMQ), fine motor quotient (FMQ), and total motor quotient (TMQ)). Association of medical variables with motor outcomes was explored. Results: Participants included 33 (58% male) children with diagnoses of biliary atresia (70%), Alagille syndrome (21%), and others (9%). Median age at LT was 10 (IQR 7.0–20.5) months. Pre‐LT >75% of children were at risk for motor delay (≤10 th percentile on AIMS/ ≥1SD below mean GMQ). Post‐LT, 52% scored ≥1 SD below the mean GMQ compared with 22% FMQ. Children at risk/delayed pre‐LT had an increased risk of motor delay on GMQ post‐LT (odds ratio 11.43, 95% CI 1.12–116.7, p  = .017). Higher INR pre‐LT correlated with lower TMQ post‐LT ( r  = −.51, p  = .003). Longer waitlist time correlated with lower FMQ post‐LT ( r  = .41, p  = .03). GMQ post‐LT and height z‐scores pre‐LT ( r  = .46, p  = .02) and post‐LT ( r  = .45, p  < .01) were positively correlated. There was no correlation with presence of ascites, weight z‐score, length of hospitalization, and age at LT. Conclusions: Young children have increased risk of motor delay pre‐LT, which may persist post‐LT. Severity of liver disease and growth delays may impact motor development, highlighting the need for ongoing rehabilitation pre‐ and post‐LT.